ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING LOAN 15 BANK DENGAN ASSETS TERBESAR DI INDONESIA - Gary Lukmanto (CALYPTRA, 2017)
Abstract – Penelitian ini bertujuan untuk mengetahui pengaruh Loan Loss Provisions, Inefficiency, Leverage, Solvency Ratio, Non – Interest Income, Size, Profitability, Inflation, GDP Growth, Interest Rate, Unemployment, Exchange Rate terhadap Non Performing Loan pada 15 b ank dengan assets terbesar di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif dan metode data pooling. Penelitian ini menggunakan sampel dari 15 bank dengan assets terbesar di Indonesia, yaitu PT Bank Mandiri (Persero),Tbk, PT Bank Rakyat Indonesia (Persero), Tbk, PT Bank Central Asia, Tbk, PT Bank Negara Indonesia (Persero), Tbk, PT Bank CIMB Niaga, Tbk, PT Bank Danamon Indonesia, Tbk, PT Panin Indonesia Bank, Tbk, PT Bank Permata, Tbk, PT Bank Internasional Indonesia, Tbk, PT Bank Tabungan Negara (Persero), PT Bank OCBC NISP, Tbk, PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk, PT Bank Bukopin, Tbk, PT Bank Mega, Tbk, dan PT Bank UOB Indonesia. Temuan dari penelitian ini menunjukkan bahwa Loan Loss Provisions dan Inflasi berpengaruh positif dan signifikan terhadap NPL. Inefficiency, Solvency Ratio, Non Interest Income, dan Size berpengaruh negatif dan tidak signifikan terhadap NPL. Leverage berpengaruh positif dan tidak signifikan terhadap NPL. Profitability berpengaruh negatif dan signifikan terhadap NPL. GDP Growth, Interest Rate, Unemployment, dan Exchange Rate berpengaruh positif dan tidak signifikan terhadap NPL. Kata Kunci: Loan Loss Provisions, Inefficiency, Leverage, Solvency Ratio, Non – Interest Income, Size, Profitability, Inflation, GDP Growth, Interest Rate, Unemployment, Exchange Rate, Non Performing Loan. Abstract –This study aimed to identify the influence of Loan Loss Provisions, Inefficiency, Leverage, Solvency Ratio, Non – Interest Income, Size, Profitability, Inflation, GDP Growth, Interest Rate, Unemployment, Exchange Rate to Non Performing Loans on the top 15 banks with the bigger assets in Indonesia. This study used a quantitative approach and pooling data method. The top 15 banks with the bigger assets are PT Bank Mandiri (Persero),Tbk, PT Bank Rakyat Indonesia (Persero), Tbk, PT Bank Central Asia, Tbk, PT Bank Negara Indonesia (Persero), Tbk, PT Bank CIMB Niaga, Tbk, PT Bank Danamon Indonesia, Tbk, PT Panin Indonesia Bank, Tbk, PT Bank Permata, Tbk, PT Bank Internasional Indonesia, Tbk, PT Bank Tabungan Negara (Persero), PT Bank OCBC NISP, Tbk, PT Bank Pembangunan Daerah Jawa Barat dan Banten, Tbk, PT Bank Bukopin, Tbk, PT Bank Mega, Tbk, dan PT Bank UOB Indonesia in the period 2003 – 2013. The results of this research indicate that Loan Loss Provisions and Inflation had positive and significant effect to NPL. Inefficiency, Solvency Ratio, Non Interest Income, and Size had negative and not significant to NPL. Leverage had positive and not significant to NPL. Profitability had negative and significant to NPL. GDP Growth, Interest Rate, Unemployment, and Exchange Rate had positive and not significant to NPL. Key Words: Loan Loss Provisions, Inefficiency, Leverage, Solvency Ratio, Non – Interest Income, Size, Profitability, Inflation, GDP Growth, Interest Rate, Unemployment, Exchange Rate, Non Performing Loan.